BLENDING EDUCATION AND ARTIFICIAL INTELLIGENCE - Khanchandani, Anu (Global journal of Business and Integral Security, 2024)
This article explores the transformative impact of AI in education, focusing on the shift towards data-driven assessments and personalized learning. AI's analytical power facilitates a deeper understanding of student performance, refining the accuracy and efficiency of evaluations. It also predicts challenges to proactively tailor support, ensuring a more adaptive learning experience. Moreover, AI-driven chatbots using NLP enhance student support, available 24/7, reflecting a democratized access to information. The article further discusses personalized learning, where AI tailors educational pathways and goals to individual student needs, and the role of AI in matching student skillsets with internships, providing bespoke career guidance. Additionally, it delves into the use of AR and VR in creating interactive teaching experiences and AI's capability in content generation, highlighting the shift towards a more engaging, accessible, and customized learning experience. Overall, AI promises to make education more adaptable, inclusive, and aligned with the aspirations and needs of students.